AEI Zeolite Synthesis

By recycling and reusing the mother liquor during the AEI zeolite synthesis process, the relative yield of silica and SDA is improved, the problems of high manufacturing costs and great environmental impact in the prior art are solved, and more efficient and environmentally friendly AEI zeolites are achieved. Synthesis method.

CN112939011BActive Publication Date: 2025-02-11JOHNSON MATTHEY PLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110107855.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2013-11-22
Filing Date
2014-10-31
Publication Date
2025-02-11
Estimated Expiration
2034-10-31

AI Technical Summary

Technical Problem

In the existing AEI zeolite synthesis methods, the relative yields of silica and structural guide agent (SDA) are low, resulting in high manufacturing costs and great environmental impact.

Method used

The relative yields of silica and SDA are increased by recovering the mother liquor at the end of the zeolite crystallization reaction and reusing it in the subsequent zeolite crystallization reaction.

Benefits of technology

The relative yields of silica and SDA in AEI zeolite synthesis methods have been significantly improved, reducing manufacturing costs and reducing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112939011B_ABST
    Figure CN112939011B_ABST
Patent Text Reader

Abstract

A new method for synthesizing AEI zeolites is provided which gives high overall relative yields based on silica and structure directing agent.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the Chinese patent application with application number 201410601423.9, application date October 31, 2014, and invention name “AEI zeolite synthesis”. Field of the Invention

[0002] The present invention relates to a method for synthesizing a molecular sieve having an AEI framework, a unique molecular sieve produced by the method, and the use of the molecular sieve as a catalyst. Background of the Invention

[0003] Zeolites are crystalline or quasicrystalline aluminosilicates composed of repeated SiO4 and AlO4 tetrahedral units. These units are linked together to form a framework with regular crystalline cavities and molecular-sized channels. Many types of synthetic zeolites have been synthesized, and each has a unique framework based on a specific arrangement of its tetrahedral units. Typically, each framework type is assigned a unique three-letter code (e.g., "AEI") by the International Zeolite Association (IZA).

[0004] Zeolites have a variety of industrial applications, and certain framework zeolites such as AEI are known to be effective catalysts for treating combustion exhaust gases in industrial applications including internal combustion engines, gas turbines, coal-fired power stations, etc. In one example, nitrogen oxides (NO x ) can be controlled by the so-called selective catalytic reduction (SCR) method, whereby NO x The compound is contacted with a reducing agent in the presence of a zeolite catalyst.

[0005] Synthetic AEI zeolites are produced using structure directing agents (SDAs), which are also referred to as "templates" or "templating agents". SDAs are typically complexing organic molecules that direct or direct the molecular shape and pattern of the zeolite framework. Typically, the SDA acts as a mold around which the zeolite crystals are formed. After the crystals are formed, the SDA is removed from the crystal's internal structure, leaving behind a porous aluminosilicate cage of molecules.

[0006] In a typical synthesis technique, solid zeolite crystals are precipitated from a reaction mixture comprising a framework reactant (e.g., a silica source and an alumina source), a hydroxide ion source (e.g., NaOH), and SDA. This synthesis technique typically requires several days (depending on factors such as the crystallization temperature) to achieve the desired crystallization. When crystallization is complete, the solid precipitate containing the zeolite crystals is filtered out, and the remaining mother liquor is discarded. The discarded mother liquor contains unused SDA, which is often degraded due to the harsh reaction conditions.

[0007] Known SDAs for AEI zeolite synthesis are relatively expensive and constitute a major part of the zeolite manufacturing costs. In addition, conventional methods for synthesizing zeolite AEI have relatively poor yields on silica, a key component of the reaction mixture, which also affects manufacturing costs. It is therefore desirable to reduce the cost of the synthesis process, preferably by means that have less environmental impact. The present invention particularly meets this need. Summary of the invention

[0008] Applicants have discovered certain means for increasing the relative yields based on silica and / or SDA in the AEI zeolite synthesis process. As used herein, the term "relative yield" in relation to a chemical reactant means the amount of reactant (or its derivative) that is incorporated into the desired product as a proportion of the total amount of reactants introduced in the chemical process. Thus, the relative yield of a reactant can be calculated as follows:

[0009] (Relative yield) R =(R P ) / (R T )

[0010] Where R is the reactant, R P is the total weight of reactant R (or its derivative) mixed into the desired product, and R T It is the total weight of the reactant R introduced in the chemical process. Here, the relative yield is used to measure the efficiency of the chemical process using the reactant. The term "total relative yield" represents the overall relative yield for a chemical process, including, for example, multiple sequential zeolite synthesis batch reactions. Therefore, the total relative yield in terms of silica represents the total amount of silica mixed into the total amount of zeolite produced throughout one or more sequential batches (relative to the amount of silica remaining in the discarded mother liquor) relative to the total amount of silica introduced into the process as a whole. Similarly, the total relative yield in terms of SDA represents the amount of SDA used directly in the zeolite framework throughout one or more sequential batches (relative to the amount of SDA retained in the discarded mother liquor) relative to the amount of silica introduced into the process as a whole. The total amount of these materials typically corresponds to the total weight of the material.

[0011] In certain aspects of the invention, the relative yield of silica and / or SDA in the AEI zeolite synthesis process is increased by recovering the mother liquor at the end of the zeolite crystallization reaction and reusing the mother liquor for subsequent zeolite crystallization reactions. As used herein, "mother liquor" is the non-precipitated portion of the reaction mixture that remains after crystallization. In some embodiments, the mother liquor is the remaining portion of the reaction mixture after filtering out or otherwise separating the zeolite crystals. Therefore, the mother liquor contains only a portion of the original solutes, and the remaining majority is mixed into the precipitate.

[0012] The mother liquor produced by conventional AEI zeolite synthesis processes contains degraded SDA and is generally not reusable. However, the present inventors have discovered that certain SDAs are resistant to degradation and can therefore be reused in subsequent zeolite synthesis batches. SDAs useful in the present invention include cationic N,N-dimethyl-3,5-dimethylpiperidinium, N,N-dimethyl-2-(2-hydroxyethyl)piperidinium, N,N-dimethyl-2-ethylpiperidinium and 2,2,4,6,6-pentamethyl-2-azabicyclo[3.2.1]octane. Surprisingly, these SDAs retain their effectiveness even after portions of the mother liquor have been reused several times.

[0013] Thus, a zeolite synthesis method is provided, comprising the steps of: (a) forming an AEI zeolite reaction mixture from an AEI synthesis process, comprising a mother liquor or a portion thereof, wherein the mother liquor or a portion thereof comprises an AEI structure directing agent; (b) reacting the mixture under crystallization conditions to form a batch of zeolite crystals having an AEI framework and a subsequent mother liquor; and optionally (c) separating the zeolite crystals having an AEI framework from the subsequent mother liquor; and (d) using the subsequent mother liquor or a portion thereof to synthesize one or more sequential batches of zeolite crystals having an AEI framework. Preferably, the mother liquor is reused in a series of sequential AEI zeolite synthesis batch reactions such that the total relative yield based on silica is at least about 60%, and / or the total relative yield based on structure directing agent is at least about 40%.

[0014] In another aspect of the present invention, a method for achieving a high overall relative yield based on silica in an AEI zeolite synthesis process is provided, comprising the steps of: (a) preparing a mixture comprising (i) at least one aluminum source, (ii) at least one silica source, (iii) at least one hydroxide ion source, and (iv) an AEI structure directing agent (SDA); and (b) reacting the mixture under crystallization conditions to form zeolite crystals having an AEI framework and a silica to alumina ratio (SAR) of about 8 to about 50, and a mother liquor, wherein the reaction affords an overall relative yield of at least about 60% based on silica.

[0015] In yet another aspect of the present invention, there is provided a novel aluminosilicate zeolite crystal having an AEI framework, an aspect ratio (L / D) of less than about 3, and optionally a silica to alumina ratio of about 8-50. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1A -C shows an embodiment of the present invention which utilizes mother liquor recycle; and

[0017] Figure 2 An embodiment of the present invention is shown having a series of multiple zeolite synthesis reactions. DETAILED DESCRIPTION

[0018] In one aspect, the present invention is an improved process for synthesizing AEI zeolites. Preferably, the present invention includes the use of certain reactants to improve the relative yields based on silica and / or SDA compared to the use of conventional reactants. In one example, the overall relative yield can be improved by selecting an SDA that can be efficiently recycled, thereby reducing the total amount of SDA required for a sequential multi-batch AEI synthesis process.

[0019] In certain embodiments, the method comprises the sequential steps of: (a) forming an AEI zeolite reaction mixture comprising a mother liquor from an AEI synthesis process, wherein the mother liquor comprises an AEI structure directing agent; and (b) reacting the mixture under crystallization conditions to form a batch of zeolite crystals having an AEI framework and a subsequent mother liquor. The precipitated zeolite crystals are preferably separated from the subsequent mother liquor by any conventional technique such as filtration. In order to improve the overall efficiency of the method, the subsequent mother liquor or a portion thereof is used to synthesize one or more sequential batches of zeolite crystals having an AEI framework.

[0020] As used herein, the term "AEI" refers to an AEI-type framework approved by the International Zeolite Association (IZA) Structure Committee, and the term "AEI zeolite" means that the main crystalline phase is an aluminosilicate of AEI. In certain embodiments, other crystalline phases such as FAU may also be present, but the main crystalline phase comprises at least about 90% by weight of AEI, preferably at least about 95% by weight of AEI, and even more preferably at least about 98 or at least about 99% by weight of AEI. The molecular sieve may include a small amount of FAU, preferably less than 5% by weight, and even more preferably less than about 2% by weight or even less than about 1% by weight. Preferably, the AEI molecular sieve is substantially free of other crystalline phases, and does not have two or more types of frameworks that coexist. With respect to other crystalline phases, "substantially free" means that the molecular sieve comprises at least 99% by weight of AEI.

[0021] As used herein, the term "zeolite" refers to a synthetic aluminosilicate molecular sieve having a framework composed of alumina and silica (i.e., repeating SiO4 and AlO4 tetrahedral units), and preferably having a silica to alumina ratio (SAR) of at least 8, such as about 8 to about 50.

[0022] The zeolites of the present invention are not silica-aluminophosphates (SAPOs) and therefore do not have measurable amounts of phosphorus in their frameworks. That is, the zeolite framework does not have phosphorus as a regular repeating unit and / or does not have phosphorus in an amount that would affect the basic physical and / or chemical properties of the material, particularly with respect to the selective reduction of NO over a wide temperature range. xIn certain embodiments, the amount of framework phosphorus is less than 0.1 wt %, preferably less than 0.01 or less than 0.001 wt %, based on the total weight of the zeolite.

[0023] As used herein, zeolite contains no or substantially no framework metals except aluminum. Therefore, "zeolite" is different from "metal-substituted zeolite", wherein the latter comprises such a framework, which comprises one or more non-aluminum metals substituted into the zeolite framework. In certain embodiments, the zeolite framework or the entire zeolite contains no or substantially no transition metals, including copper, nickel, zinc, iron, tungsten, molybdenum, cobalt, titanium, zirconium, manganese, chromium, vanadium, niobium, and tin, bismuth and antimony; contains no or substantially no noble metals, including platinum group metals (PGM), such as ruthenium, rhodium, palladium, indium, platinum, and such as gold and silver noble metals; and contains no or substantially no rare earth metals such as lanthanum, cerium, praseodymium, neodymium, europium, terbium, erbium, ytterbium and yttrium.

[0024] The zeolite synthesized by the method of the present invention may include one or more non-framework alkali metals and / or alkaline earth metals. These metals are typically introduced into the reaction mixture together with a hydroxide ion source. Examples of such metals include sodium and potassium, as well as magnesium, calcium, strontium, barium, lithium, cesium and rubidium.

[0025] It is generally desirable to remove the alkali metal cation by ion exchange and replace it with hydrogen, ammonium or any desired metal ion. Therefore, the zeolite of the present invention can be a Na-type zeolite, a K-type zeolite, etc., or can be an H-type zeolite, an ammonium-type zeolite or a metal-exchanged zeolite. Typical ion exchange techniques include contacting the synthetic zeolite with a solution containing a salt of one or more desired replacement cations. Although a wide variety of salts can be used, chlorides and other halides, nitrates and sulfates are particularly preferred. Representative ion exchange techniques are well known in the art. Ion exchange occurs after synthesis and can be performed before or after calcination of the zeolite. After contact with the salt solution of the desired replacement cation, the zeolite is typically washed with water and dried at a temperature of 65°C to about 315°C. After washing, the zeolite can be calcined in air or an inert gas at a temperature of about 200°C to 820°C for 1-48 hours or more to produce a catalytically active and stable product.

[0026] The zeolite reaction mixture and / or mother liquor (derived from the AEI synthesis process) typically comprises at least one silica source, at least one alumina source, at least one SDA that can be used to form an AEI framework, and at least one hydroxide ion source. However, it should be understood that the synthesis method described herein is not necessarily limited to aluminosilicates, but can also be applied to the synthesis of other molecular sieves having an AEI structure, such as iron silicates, titanosilicates, vanadosilicates, and borosilicates. Therefore, more generally, the reaction mixture from which the molecular sieve is crystallized comprises an active source of at least one tetravalent oxide or a mixture of tetravalent oxides (e.g., silicon oxide, germanium oxide, or a mixture thereof) and at least one trivalent oxide or a mixture of trivalent oxides (e.g., aluminum oxide, boron oxide, gallium oxide, vanadium oxide, iron oxide, or a mixture thereof).

[0027] Go to Figure 1A -C, shows a method according to one embodiment of the present invention. Here, an AEI zeolite reaction mixture 114 comprising a mother liquor 112 from an AEI synthesis process is reacted in a reactor 100 under crystallization conditions to form a batch of zeolite crystals 102 having an AEI framework and a subsequent mother liquor 122. In another embodiment, the method further includes the steps of separating the zeolite crystals 102 having an AEI framework from the subsequent mother liquor 122, and using the subsequent mother liquor 122 or a portion thereof to synthesize one or more sequential batches of zeolite crystals having an AEI framework. Preferably, the mother liquor 112 and the subsequent mother liquor 122 contain at least one SDA that can be used to form an AEI zeolite. The mother liquor 112 and / or the subsequent mother liquor 122 may further contain at least one silica source, at least one alumina source, and at least one hydroxide ion source. In order to achieve the desired ratio of reactants in the mixture 114, the mother liquor 112 can be combined with the feed stream 110, which contains at least one silica source, at least one alumina source, at least one SDA that can be used to form the AEI framework, and / or at least one hydroxide ion source. Similarly, the post-mother liquor 122 can be combined with the supplemental feed 130 to achieve the appropriate balance of reactants, which contains at least one silica source, at least one alumina source, at least one SDA that can be used to form the AEI framework, and / or at least one hydroxide ion source. Typically, the feed streams 110 and / or 130 will contain such amounts of silica source, alumina source, and SDA source that are equivalent to the amount of these components removed from the reactor as precipitates (e.g., mixed into the zeolite crystals).

[0028] In one embodiment, the post-formed mother liquor 122 is retained in the reactor and receives supplemental feed. The second AEI zeolite reaction mixture is then reacted in the reactor 100 under crystallization conditions to form a sequential batch of zeolite crystals having an AEI framework. An alternative embodiment is shown in Figure 1CIn the embodiment of the present invention, the mother liquor 122 is removed from the reactor 100 and mixed with the supplemental feed 130 to form the second AEI zeolite reaction mixture 132 before entering the reactor 100.

[0029] Figure 2 Yet another embodiment is shown in which a first feed stream 110 is combined with a mother liquor 112 from an AEI synthesis process to form a first AEI zeolite reaction mixture 114. The combination of the first feed stream and the mother liquor 112 may be performed prior to introduction into the reactor 100, or may be performed within the reactor 100. The first AEI zeolite reaction mixture 114 is reacted in the reactor 100 under crystallization conditions to form a first batch of zeolite crystals having an AEI framework 120 and a first post-formed mother liquor 122. The first post-formed mother liquor 122 is combined with a first make-up stream 210 to form a second AEI zeolite reaction mixture 214. The combination of the first feed stream and the second mother liquor 122 may be performed prior to introduction into the reactor 200, or may be performed within the reactor 200. The second AEI zeolite reaction mixture 214 is reacted in the reactor 200 under crystallization conditions to form a second batch of zeolite crystals having an AEI framework 220 and a second post-formed mother liquor 222. The second post-formed mother liquor 222 is combined with the second make-up stream 310 to form a third AEI zeolite reaction mixture 314. The combination of the second feed stream and the third mother liquor 222 may be performed prior to introduction into the reactor 300, or may be performed within the reactor 300. The third AEI zeolite reaction mixture 314 is reacted in the reactor 300 under crystallization conditions to form a third batch of zeolite crystals having an AEI framework 320 and a second post-formed mother liquor 322.

[0030] Figure 2 The method shown includes three AEI zeolite syntheses performed in sequence, wherein the mother liquor or a portion thereof from one AEI synthesis is reused in a subsequent AEI zeolite synthesis. However, the method of the present invention is not necessarily limited to a specific number of AEI zeolite syntheses and mother liquor reuses. Alternatively, the number of AEI zeolite syntheses performed in sequence and mother liquor reuses will depend on the desired total relative yield based on reactants. Typically, increasing the number of times the mother liquor is reused will increase the total relative yield based on reactants. Preferably, the total relative yield of the total process based on silica is at least about 60%, such as at least about 75%, at least about 90%, at least about 95%, about 60-99%, about 60-80%, about 80-90%, about 90-99%, about 90-95% or about 95-99%. Preferably, the overall relative yield of the overall process based on SDA will be at least about 40%, such as at least about 60%, at least about 80%, at least about 90%, about 40-99%, about 40-60%, about 60-80%, about 80-90%, about 90-95% or about 95-99%.

[0031] Suitable silicon dioxide sources include, but are not limited to, fumed silica, silicates, precipitated silica, colloidal silica, silica gel, dealuminate zeolites such as dealuminate Y zeolite, and silicon hydroxides and alkoxides. Silicon dioxide sources that produce high relative yields are preferred. Typical alumina sources are also generally known, including aluminates, alumina, other zeolites such as FAU zeolite, aluminum colloids, boehmite, pseudoboehmite, aluminum hydroxide, aluminum salts such as aluminum sulfate and aluminum chloride, aluminum hydroxides and alkoxides, alumina gels.

[0032] Typically, a hydroxide ion source such as an alkali metal hydroxide and / or an alkaline earth metal hydroxide, including hydroxides of sodium, potassium, lithium, cesium, rubidium, calcium and magnesium, is used in the reaction mixture. However, this component can be omitted, as long as the basicity of equivalent is maintained. In certain embodiments, a template can be used to provide hydroxide ions. Therefore, it can be beneficial to ion exchange, such as for example, a halide for hydroxide ions, thereby reducing or eliminating the required alkali metal hydroxide amount. Alkali metal cations or alkaline earth metal cations can be a part of the crystalline oxide material of the original state of synthesis, to balance the valence electron charge therein.

[0033] Salts, particularly alkali metal halides such as sodium chloride, may also be added to the reaction mixture, or formed therein. Preferably, the AEI zeolite reaction mixture is free or substantially free of fluorine, fluorine-containing compounds and fluoride ions.

[0034] The reaction mixture may be in the form of a solution, a gel or a paste, and preferably a gel. AEI may be prepared from a reaction mixture having a composition as shown in Table 1. The silicon- and aluminum-containing reactants are denoted as SiO2 and Al2O3, respectively.

[0035] Table 1

[0036] Typical Preferred <![CDATA[SiO2 / Al2O3]]> 10-100 15-60 <![CDATA[OH - / SiO2]]> 0.5-1.0 0.6-0.8 <![CDATA[SDA / SiO2]]> 0.05-0.50 0.10-0.20 <![CDATA[Alkali metal cation / SiO2]]> 0.10-1.0 0.15-0.35 <![CDATA[H2O / SiO2]]> 20-80 30-40

[0037] Preferably, the supplemental feed contains an amount of silica, alumina, SDA, alkali metal cations and / or water to achieve the desired component ration when combined with the reused mother liquor. In order to achieve an appropriate component balance, the concentration of one or more components or by-products may be removed from the mother liquor prior to combining with the supplemental feed. For example, the concentration of alkali metal cations or water in the mother liquor may be reduced to achieve the desired component ratio in the AEI synthesis reaction mixture.

[0038] Reaction temperatures, mixing times and speeds and other process parameters that are suitable for conventional CHA synthesis techniques are also generally suitable for the present invention. Typically, the reaction mixture is maintained at an elevated temperature until AEI zeolite crystals are formed. Hydrothermal crystallization is typically carried out under autogenous pressure at a temperature of about 75-220° C., such as about 120-160° C. for several hours, such as about 0.1-20 days and preferably about 0.25-3 days. Preferably, the zeolite is prepared using gentle stirring or agitation.

[0039] During the hydrothermal crystallization step, AEI crystals may be allowed to spontaneously nucleate from the reaction mixture. Using AEI crystals as seed material may be advantageous in reducing the time necessary for complete crystallization to occur. When used as seeds, AEI crystals are added in an amount of 0.1-10% by weight of the silica used in the reaction mixture.

[0040] Once the zeolite crystals are formed, the solid product is separated from the reaction mixture by standard mechanical separation techniques such as filtration. The crystals are washed with water and then dried for a few seconds to a few minutes (e.g., flash drying for 5 seconds to 10 minutes) or a few hours (e.g., oven drying at 75-150° C. for about 4-24 hours) to obtain as-synthesized AEI zeolite crystals. The drying step can be carried out at atmospheric pressure or under vacuum.

[0041] It will be understood that the foregoing order of steps and the various time periods and temperature values ​​described above are exemplary only and may vary.

[0042] The synthesis method of the present invention produces a novel AEI zeolite crystal having a unique morphology for an AEI type zeolite. Specifically, the average length to diameter (L / D) aspect ratio of the novel AEI zeolite crystal is less than or equal to 3, such as less than or equal to 2.5, less than or equal to 2.0, less than or equal to 1.5, less than or equal to 1.0. Preferably, the L / D aspect ratio is calculated based on the measurement of the two crystal dimensions using the following microscopy method.

[0043] Preferred microscopic methods include SEM and TEM. These methods typically require the measurement of a large number of crystals, and for each crystal measured, the value can be evaluated in two dimensions. In addition, in order to more completely characterize the crystal size of a batch of crystals, the average L / D aspect ratio should be calculated, as well as the degree of deviation from the average value in terms of crystal size distribution. For example, the measurement by SEM includes the morphology of the material being examined at a high magnification (typically 1000× to 10,000×). The SEM method can be performed as follows: a representative portion of the zeolite powder is distributed on a suitable carrier so that a single particle is reasonably evenly spread throughout a field of view of 1000× to 10,000× magnification. From this particle group (population), a statistically significant sample (n) of random single crystals (e.g., 50) was checked, and the longest dimension of the single crystal parallel to the horizontal line of the straight edge (ignoring the twin boundary) was measured, recorded as the crystal length. The diameter of the crystal along the length axis is then measured using a similar technique. Based on these measurements, the arithmetic mean and deviation of the sample are calculated. In certain embodiments, the samples also have a mathematical deviation of less than about 1, preferably less than 0.5, and even more preferably less than about 0.2 on average.

[0044] The AEI zeolite crystals produced according to the method are uniform, have little to no twins and / or multiple twins, and have little aggregation. The morphology and especially the low L / D ratio of the crystals are expected to provide better catalytic performance in certain applications.

[0045] The average crystal size of the AEI zeolite crystals produced according to the methods described herein is about 0.05 to about 5 μm, such as about 0.5 to about 5 μm, about 0.1 to about 1 μm and about 1 to about 5 μm. In certain embodiments, large crystals are ground to an average size of about 1.0 to about 1.5 microns using a jet mill or other particle-on-particle grinding technique to facilitate washcoating of the catalyst-containing slurry onto a substrate such as a flow-through monolith.

[0046] The AEI zeolite synthesized by the methods described herein preferably has a silica to alumina ratio (SAR) of at least 8, e.g., from about 8 to about 50, from about 10 to about 35, or from about 15 to about 25. The SAR can be selectively achieved based on the composition of the starting synthesis mixture and / or by adjusting other process variables. The silica to alumina ratio of the zeolite can be determined by conventional analysis. The ratio is intended to represent as closely as possible the ratio in the hard atomic framework of the zeolite crystal, and excludes silicon or aluminum in the binder (for catalyst applications) in the channels or in cations or other forms.

[0047] AEI zeolite can be used as a catalyst in certain applications. Dried AEI crystals are preferably calcined for use, but can also be used without calcination. The AEI catalyst can also be used without or with post-synthesis metal exchange. Therefore, in certain aspects of the present invention, a catalyst comprising an AEI zeolite is provided, wherein the AEI zeolite does not contain or is substantially free of any exchanged metal, particularly post-synthesis exchanged or impregnated metals. In other embodiments, a catalyst comprising an AEI zeolite is provided, the zeolite containing one or more catalytic metal ions exchanged or otherwise impregnated into the channels and / or cavities of the zeolite. Examples of metals that may be post-zeolite synthesis exchanged or impregnated include transition metals, including copper, nickel, zinc, iron, tungsten, molybdenum, cobalt, titanium, zirconium, manganese, chromium, vanadium, niobium, as well as tin, bismuth and antimony; noble metals, including platinum group metals (PGMs), such as ruthenium, rhodium, palladium, indium, platinum, and noble metals such as gold and silver; alkaline earth metals such as beryllium, magnesium, calcium, strontium and barium; and rare earth metals such as lanthanum, cerium, praseodymium, neodymium, europium, terbium, erbium, ytterbium and yttrium. Preferred transition metals for post-synthesis exchange are base metals, and preferred base metals include those selected from manganese, iron, cobalt, nickel and mixtures thereof.

[0048] The transition metal may be present in an amount of about 0.1 to about 10 wt %, such as about 0.5 to about 5 wt %, about 0.1 to about 1.0 wt %, about 2.5 to about 3.5 wt %, and about 4.5 to about 5.5 wt %, wherein the wt % is relative to the total weight of the zeolitic material.

[0049] Particularly preferred exchange metals include copper and iron, especially when combined with calcium and / or cerium, and especially when transition metals (T M ) and alkali metals (A M )T M :A M This is especially true when the molar ratio is from about 15:1 to about 1:1, such as from about 10:1 to about 2:1, from about 10:1 to about 3:1, or from about 6:1 to about 4:1.

[0050] The metal incorporation may be added to the molecular sieve post-synthesis via any known technique such as ion exchange, impregnation, isomorphous substitution, and the like.

[0051] These exchanged metal cations are different from the metal that makes up the molecular framework of the zeolite, and thus metal-exchanged zeolites are different from metal-substituted zeolites.

[0052] For embodiments where the catalyst is part of a washcoat composition, the washcoat may further comprise a binder comprising Ce or ceria. For this embodiment, the Ce-containing particles in the binder are significantly larger than the Ce-containing particles in the catalyst.

[0053] The catalyst of the present invention is particularly useful in heterogeneous catalytic reaction systems (i.e., solid catalysts in contact with gaseous reactants). In order to improve the contact surface area, mechanical stability and / or fluid flow characteristics, the catalyst can be located on and / or in a substrate, preferably a porous substrate. In certain embodiments, a washcoat containing the catalyst is applied to an inert substrate such as a corrugated metal sheet or a honeycomb cordierite block. Alternatively, the catalyst is kneaded with other components such as fillers, adhesives and reinforcing agents into an extrudable paste, which is then extruded through a die to form a honeycomb block. Therefore, in certain embodiments, a catalyst article is provided, which comprises the AEI catalyst described herein coated on and / or mixed into a substrate.

[0054] Certain aspects of the present invention provide a catalytic washcoat. The washcoat comprising the AEI catalyst described herein is preferably a solution, suspension or slurry. Suitable coatings include surface coatings, coatings that penetrate into a portion of a substrate, coatings that penetrate into a substrate or some combination thereof.

[0055] A washcoat may also include non-catalytic components such as fillers, binders, stabilizers, rheology modifiers and other additives, including one or more of the following: alumina, silica, non-zeolitic silica alumina, titania, zirconia, ceria. In certain embodiments, the catalyst composition may include pore formers such as graphite, cellulose, starch, polyacrylates and polyethylene, etc. These additional components do not necessarily catalyze the desired reaction, but instead improve the effectiveness of the catalytic material, for example by increasing its operating temperature range, increasing the contact surface area of ​​the catalyst, increasing the adhesion of the catalyst to the substrate, etc. In preferred embodiments, the washcoat loading is >0.3 g / in 3 , for example >1.2g / in 3 、>1.5g / in 3 、>1.7g / in 3 or >2.00g / in 3 , and preferably <3.5 g / in 3 , e.g. <2.5g / in 3 In certain embodiments, the washcoat is applied at about 0.8-1.0 g / in 3 1.0-1.5g / in 3 or 1.5-2.5g / in 3 The loading amount is applied to the substrate.

[0056] The two most commonly used substrate designs to which the catalyst can be applied are plate-like and honeycomb-like. Preferred substrates, particularly substrates for mobile applications, include flow-through monoliths having so-called honeycomb geometry, which contain a plurality of adjacent, parallel channels that are open at both ends and generally extend from the inlet face of the substrate to the outlet face, and produce a high surface area to volume ratio. For some applications, the honeycomb flow-through monolith preferably has a high pore density, such as about 600-800 pores / square inch, and / or an average inner wall thickness of about 0.18-0.35 mm, preferably about 0.20-0.25 mm. For some other applications, the honeycomb flow-through monolith preferably has a low pore density of about 150-600 pores / square inch, more preferably about 200-400 pores / square inch. Preferably, the honeycomb monolith is porous. In addition to cordierite, silicon carbide, silicon nitride, ceramics and metals, other materials that can be used for the substrate include aluminum nitride, silicon nitride, aluminum titanate, α-alumina, mullite such as acicular mullite, cesium garnet, metal ceramics (thermet) such as Al2OsZFe, Al2O3 / Ni or B4CZFe, or a composite comprising any two or more fragments thereof. Preferred materials include cordierite, silicon carbide and aluminum titanate.

[0057] Compared to honeycomb, plate-type catalysts have lower pressure drop and are less prone to clogging and fouling, which is advantageous in high-efficiency fixed applications, but the plate-like configuration will be much larger and more expensive. Honeycomb configurations are typically smaller than plate-type, which is an advantage in mobile applications, but have higher pressure drop and are more prone to clogging. In certain embodiments, the plate-like substrate is composed of metal, preferably corrugated metal.

[0058] In certain embodiments, the present invention is a catalyst article made by the methods described herein. In a specific embodiment, the catalyst article is produced by a method comprising the steps of applying an AEI catalyst composition, preferably in the form of a washcoat, as a layer to a substrate before or after at least one additional layer of another composition for treating exhaust gas is applied to the substrate. The one or more catalyst layers (including the AEI catalyst layer) on the substrate are arranged in a continuous layer. As used herein, the term "continuous" in relation to the catalyst layers on the substrate means that each layer is in contact with its adjacent layer and the catalyst layers are located on top of one another on the substrate as a whole.

[0059] In certain embodiments, the AEI catalyst is disposed on a substrate as a first layer or first zone, and another composition such as an oxidation catalyst, a reduction catalyst, a scavenging component, or a NO xThe storage component is located on the substrate as a second layer or second zone. As used herein, the terms "first layer" and "second layer" are used to describe the relative position of the catalyst layer in the catalyst article relative to the normal direction of the exhaust gas flowing through, through the catalyst article and / or flowing from the catalyst article. Under normal exhaust gas flow conditions, the exhaust gas contacts the first layer before contacting the second layer. In certain embodiments, the second layer is applied to an inert substrate as a bottom layer, and the first layer is a top layer, which is applied to the second layer as a continuous series of sublayers. In such an embodiment, before contacting the second layer, the exhaust gas penetrates (and therefore contacts) the first layer, and then passes through the first layer back to leave the catalyst assembly. In other embodiments, the first layer is a first zone located on the upstream portion of the substrate, and the second layer is located on the substrate as a second zone, wherein the second zone is downstream of the first zone.

[0060] In another embodiment, the catalyst article is produced by a process comprising the steps of applying an AEI catalyst composition, preferably in the form of a washcoat, to a substrate as a first zone, followed by applying at least one additional composition for treating exhaust gas to the substrate as a second zone, wherein at least a portion of the first zone is downstream of the second zone. Alternatively, the AEI catalyst composition can be applied to the substrate in a second zone containing the additional composition downstream of the first zone. Examples of additional compositions include oxidation catalysts, reduction catalysts, scavenging components (e.g., for sulfur, water, etc.), or NO x Storage components.

[0061] In order to reduce the amount of space required for the exhaust system, in certain embodiments, a single exhaust component is designed to perform more than one function. For example, an SCR catalyst is applied to a wall-flow filter substrate rather than a flow-through substrate to provide a single substrate with two functions (i.e., catalyzing the reduction of NO in the exhaust gas). x concentration and mechanical removal of soot from the exhaust gas) to reduce the overall size of the exhaust treatment system. Therefore, in certain embodiments, the substrate is a honeycomb wall-flow filter or partial filter. Wall-flow filters are similar to flow-through honeycomb substrates in that they contain multiple adjacent parallel channels. However, the channels of the flow-through honeycomb substrate are open at both ends, while the channels of the wall-flow substrate have a closed end, wherein the closure exists in an alternating manner on the opposite ends of adjacent channels. The alternating closed channel ends prevent the gas entering the inlet face of the substrate from flowing directly through the channel and leaving. Instead, the exhaust gas enters the front of the substrate and travels to about half of the channel, where it is driven through the channel wall, then enters the second half of the channel, and exits the back of the substrate.

[0062] The substrate wall has a porosity and pore size that is permeable to gas, but captures most of the particulate matter, such as soot, in the gas as it passes through the wall. The preferred wall-flow substrate is a high efficiency filter. The preferred efficiency of the wall-flow filter used in the present invention is at least 70%, at least about 75%, at least about 80%, or at least about 90%. In certain embodiments, the efficiency will be about 75-about 99%, about 75-about 90%, about 80-about 90%, or about 85-about 95%. Here, the efficiency is relative to soot and other particles of similar size and relative to the concentration of particles typically present in conventional diesel exhaust. For example, the size of the particles in diesel exhaust can be 0.05 microns-2.5 microns. Therefore, the efficiency can be based on this range or sub-range, such as 0.1-0.25 microns, 0.25-1.25 microns, or 1.25-2.5 microns.

[0063] Porosity is a measure of the percentage of void space in a porous substrate and is related to back pressure in an exhaust system: generally, the lower the porosity, the higher the back pressure. Preferably, the porosity of the porous substrate is about 30 to about 80%, such as about 40 to about 75%, about 40 to about 65%, or about 50 to about 60%.

[0064] Pore ​​interconnectivity (measured as a percentage of the total void volume of the substrate) is the extent to which the pores, voids and / or channels connect to form a continuous path through the porous substrate (i.e., from the inlet face to the outlet face). The inverse of pore interconnectivity is the sum of the closed pore volume and the pore volume having conduits to only one surface of the substrate. Preferably, the pore interconnectivity volume of the porous substrate is at least about 30%, more preferably at least about 40%.

[0065] The average pore size of the porous substrate is also important for filtration. The average pore size can be determined by any acceptable means, including by mercury porosimetry. The average pore size of the porous substrate should be of a sufficiently high value to promote low back pressure while providing sufficient efficiency through the substrate itself, by promoting a soot cake layer on the substrate surface, or a combination of the two. Preferred porous substrates have an average pore size of about 10 to about 40 μm, such as about 20 to about 30 μm, about 10 to about 25 μm, about 10 to about 20 μm, about 20 to about 25 μm, about 10 to about 15 μm, and about 15 to about 20 μm.

[0066] Typically, the production of an extruded solid body containing an AEI catalyst, such as a honeycomb flow-through or wall-flow filter, comprises blending the AEI catalyst, a binder, an optional organic tackifying compound into a uniform paste, which is then added to a binder / matrix component or its precursor and optionally one or more stable cerium oxides and inorganic fibers. The blend is compacted in a mixing or kneading device or an extruder. The mixture has organic additives such as binders, pore formers, plasticizers, surfactants, lubricants, dispersants as processing aids to enhance wetting, and thus produce uniform batches. The formed plastic material is then molded, particularly using an extrusion press or an extruder including an extrusion die, and the formed molded part is dried and calcined. The organic additive is "burned off" during the calcination of the extruded solid body. The AEI zeolite catalyst can also be activated as one or more sublayers or otherwise applied to the extruded solid body, which resides on the surface or infiltrates the extruded solid body in whole or in part.

[0067] The binder / matrix component is preferably selected from cordierite, nitrides, carbides, borides, intermetallic compounds, lithium aluminosilicate, spinel, optionally doped alumina, a silica source, titania, zirconia, titania-zirconia, zircon, and mixtures of any two or more thereof. The paste may optionally contain reinforcing inorganic fibers selected from carbon fibers, glass fibers, metal fibers, boron fibers, alumina fibers, silica fibers, silica-alumina fibers, silicon carbide fibers, potassium titanate fibers, aluminum borate fibers, and ceramic fibers.

[0068] The alumina binder / matrix component is preferably gamma alumina, but may be any other transition alumina, i.e., alpha alumina, beta alumina, chi alumina, eta alumina, rho alumina, kappa alumina, theta alumina, delta alumina, lanthanum beta alumina, and mixtures of any two or more of these transition aluminas. It is preferred that the alumina is doped with at least one non-aluminum element to increase the thermal stability of the alumina. Suitable alumina dopants include silicon, zirconium, barium, lanthanides, and mixtures of any two or more thereof. Suitable lanthanide dopants include La, Ce, Nd, Pr, Gd, and mixtures of any two or more thereof.

[0069] The AEI catalyst is preferably dispersed throughout the extruded catalyst body, and preferably is dispersed uniformly throughout.

[0070] Where any of the above extruded solid bodies are made into a wall flow filter, the porosity of the wall flow filter may be 30-80%, such as 40-70%.Porosity and pore volume and pore radius may be measured, for example, using mercury intrusion porosimetry.

[0071] The AEI catalyst described herein can promote the reaction of a reducing agent (preferably ammonia) with nitrogen oxides to selectively form elemental nitrogen (N2) and water (H2O). Therefore, in one embodiment, the catalyst can be formulated to facilitate the reduction of nitrogen oxides by a reducing agent (i.e., an SCR catalyst). Examples of such reducing agents include hydrocarbons (e.g., C3-C6 hydrocarbons) and nitrogen-containing reducing agents such as ammonia and aminohydrazine or any suitable ammonia precursor, such as urea ((NH2)2CO), ammonium carbonate, ammonium carbamate, ammonium bicarbonate, or ammonium formate.

[0072] The AEI catalysts described herein also promote the oxidation of ammonia. Thus, in another embodiment, the catalyst can be formulated to favor the oxidation of ammonia with oxygen, particularly at concentrations of ammonia typically encountered downstream of an SCR catalyst (e.g., an ammonia oxidation (AMOX) catalyst, such as an ammonia slip catalyst (ASC)). In certain embodiments, the AEI catalyst is disposed as a top layer over an oxidative underlayer, wherein the underlayer comprises a platinum group metal (PGM) catalyst or a non-PGM catalyst. Preferably, the catalyst components in the underlayer are disposed on a high surface area support, including but not limited to alumina.

[0073] In yet another embodiment, SCR and AMOX are performed in series, wherein both processes use a catalyst comprising an AEI catalyst as described herein, and wherein the SCR process is performed upstream of the AMOX process. For example, the SCR formulation of the catalyst can be placed on the filter inlet side, and the AMOX formulation of the catalyst can be placed on the filter outlet side.

[0074] Therefore, a method for removing NO from the gas is provided. x A method for reducing or oxidizing NH3 by a compound, comprising contacting the gas with a catalyst composition as described herein to catalyze the reduction of NO x The compound has enough time to reduce the NO in the gas x Compounds and / or NH3 levels. In certain embodiments, a catalyst article is provided having an ammonia slip catalyst located downstream of a selective catalytic reduction (SCR) catalyst. In such an embodiment, the ammonia slip catalyst oxidizes at least a portion of any nitrogen-containing reductant that is not consumed by the selective catalytic reduction process. For example, in certain embodiments, the ammonia slip catalyst is placed on the outlet side of a wall-flow filter, and the SCR catalyst is placed on the upstream side of the filter. In certain other embodiments, the ammonia slip catalyst is placed at the downstream end of a flow-through substrate, and the SCR catalyst is placed at the upstream end of a flow-through substrate. In other embodiments, the ammonia slip catalyst and the SCR catalyst are placed on separate blocks within the exhaust system. These separate blocks can be adjacent to each other, and in contact with each other, or separated by a specific distance, provided that they are fluidly connected to each other, and provided that the SCR catalyst block is placed upstream of the ammonia slip catalyst block.

[0075] In certain embodiments, the SCR and / or AMOX process is carried out at a temperature of at least 100°C. In another embodiment, the process is carried out at a temperature of about 150°C to about 750°C. In a specific embodiment, the temperature range is about 175 to about 550°C. In another embodiment, the temperature range is 175-400°C. In yet another embodiment, the temperature range is 450-900°C, preferably 500-750°C, 500-650°C, 450-550°C or 650-850°C. Embodiments using temperatures greater than 450°C are particularly useful for treating exhaust gases from heavy-duty and light-duty diesel engines equipped with an exhaust system comprising an (optionally catalyzed) diesel particulate filter, the filter being actively regenerated, for example by injecting hydrocarbons into the exhaust system upstream of the filter, wherein the zeolite catalyst used in the present invention is located downstream of the filter.

[0076] According to another aspect of the present invention, there is provided a method for removing NO from a gas. x A method for reducing compounds and / or oxidizing NH3, comprising contacting the gas with a catalyst as described herein for a sufficient time to reduce NO in the gas x The method of the present invention may include one or more of the following steps: (a) agglomerating and / or burning soot in contact with the inlet of the catalytic filter; (b) introducing a nitrogen-containing reductant into the exhaust gas stream prior to contact with the catalytic filter, preferably without treating NO x and the intermediate catalytic step of the reducing agent; (c) in NO x Adsorbent catalyst or lean NO x (d) contacting the exhaust gas stream with a DOC to oxidize the hydrocarbon-soluble organic fraction (SOF) and / or carbon monoxide to CO2, and / or oxidize NO to NO2, which in turn can be used to oxidize particulate matter in a particulate filter; and / or reduce particulate matter (PM) in the exhaust gas; (e) contacting the exhaust gas with one or more flow-through SCR catalyst devices in the presence of a reducing agent to reduce NO in the exhaust gas. x concentration; and (f) contacting the exhaust gas with an ammonia slip catalyst (preferably downstream of the SCR catalyst) to oxidize most, if not all, of the ammonia before the exhaust gas is discharged into the atmosphere or before the exhaust gas is sent through a recirculation loop before entering / reentering the engine.

[0077] In another embodiment, all or at least a portion of the nitrogen-based reductant, particularly NH 3 , consumed in the SCR process may be replaced by NO x Adsorbent Catalyst (NAC), Lean NO xLNT or NO x The NAC components useful in the present invention include a catalyst combination of a base material (e.g., an alkali metal, an alkaline earth metal, or a rare earth metal, including an oxide of an alkali metal, an oxide of an alkaline earth metal, and combinations thereof) and a noble metal (e.g., platinum) and an optional reducing catalyst component, such as rhodium. Specific types of base materials useful in the NAC include cesium oxide, potassium oxide, magnesium oxide, sodium oxide, calcium oxide, strontium oxide, barium oxide, and combinations thereof. The noble metal is preferably present in an amount of about 10 to about 200 g / ft 3 , e.g. 20-60g / ft 3 Optionally, the catalyst may be characterized by an average noble metal concentration of about 40 to about 100 g / ft 3 .

[0078] Under certain conditions, during periodic rich regeneration events, NH3 can be x NO is produced on the adsorbent catalyst. x An SCR catalyst downstream of the adsorbent catalyst can improve the overall system NO x Reduction efficiency. In this combined system, the SCR catalyst is able to store NH3 released from the NAC catalyst during a rich regeneration event and use the stored NH3 to selectively reduce some or all of the NO x , which slips through the NAC catalyst under normal lean operating conditions.

[0079] The methods for treating exhaust gases described herein can be performed on exhaust gases from combustion processes, such as exhaust gases from internal combustion engines (whether mobile or stationary), gas turbines, and coal-fired or oil-fired power generation equipment. The methods can also be used to treat gases from industrial processes such as refining, from refinery heaters and boilers, furnaces, chemical processing industries, coking furnaces, municipal waste treatment plants and incineration equipment, etc. In a specific embodiment, the method is used to treat exhaust gases from a lean-burn internal combustion engine of a vehicle, such as a diesel engine, a lean-burn gasoline engine, or an engine powered by liquid petroleum gas or natural gas.

[0080] In certain aspects, the present invention is a system for treating exhaust gases generated by combustion processes, such as exhaust gases from internal combustion engines (whether mobile or stationary), gas turbines, coal- or oil-fired power plants, etc. Such a system includes a catalytic article comprising an AEI catalyst as described herein and at least one additional component for treating exhaust gases, wherein the catalytic article and the at least one additional component are designed to function as an associated unit.

[0081] In certain embodiments, the system includes a catalytic article comprising an AEI catalyst as described herein, a conduit for directing a flowing exhaust gas, and a source of a nitrogen-containing reductant located upstream of the catalytic article. The system may include a controller for only controlling the catalytic article when it is determined that the zeolite catalyst is capable of catalyzing NO at a desired efficiency or above a desired efficiency, for example, at temperatures above 100° C., above 150° C., or above 175° C. x During reduction, a nitrogenous reducing agent is metered into the flowing exhaust gas. The metering of the nitrogenous reducing agent can be arranged so that 60%-200% of the theoretical ammonia calculated as 1:1 NH3 / NO and 4:3 NH3 / NO2 is present in the exhaust gas entering the SCR catalyst.

[0082] In another embodiment, the system includes an oxidation catalyst (e.g., a diesel oxidation catalyst (DOC)) for oxidizing nitrogen monoxide in the exhaust gas to nitrogen dioxide, which catalyst can be located upstream of the location where the nitrogen-containing reductant is dosed into the exhaust gas. In one embodiment, the oxidation catalyst is adjusted so that, for example, at an exhaust gas temperature at the oxidation catalyst inlet of 250° C. to 450° C., a gas stream entering the SCR zeolite catalyst is obtained with a NO to NO2 volume ratio of about 4:1 to about 1:3. The oxidation catalyst can include at least one platinum group metal (or some combination thereof), such as platinum, palladium, or rhodium, coated on a flow-through monolithic substrate. In one embodiment, the at least one platinum group metal is platinum, palladium, or a combination of platinum and palladium. The platinum group metal can be supported on a high surface area washcoat component, such as alumina, zeolite, such as aluminosilicate zeolite, silica, non-zeolitic silica alumina, ceria, zirconia, titania, or a mixed oxide or composite oxide containing ceria and zirconia.

[0083] In another embodiment, a suitable filter substrate is located between the oxidation catalyst and the SCR catalyst. The filter substrate may be selected from any of those described above, such as a wall flow filter. In the case where the filter is catalyzed, for example catalyzed with an oxidation catalyst of the type described above, it is preferred that the metering location of the nitrogen-containing reductant is located between the filter and the zeolite catalyst. Alternatively, if the filter is uncatalyzed, the means for metering the nitrogen-containing reductant may be located between the oxidation catalyst and the filter.

[0084] Example

[0085] Example: Synthesis of AEI Zeolite Using N,N-Dimethyl-3,5-dimethylpiperidinium in Recycled Mother Liquor

[0086] About 36 g of dealuminated USY zeolite with a SAR of 10.7 was mixed with about 1093 g of water. For this mixture, about 195 g of N, N-dimethyl-3,5-dimethylpiperidinium template and about 427 g of liquid sodium silicate (28.8 wt% SiO2) were slowly poured into the above mixture under stirring. The resulting mixture was then heated to 145° C. in a sealed stainless steel reactor under stirring at 200 rpm. After 2 days of crystallization, the resulting crystallization mixture was transferred to a separatory funnel. Under static conditions, the solid sediment and the top transparent liquid layer were separated within a few hours. Most of the transparent mother liquor was collected and referred to as the first mother liquor (ML-P1).

[0087] The solids in the bottom slurry were recovered and confirmed to be AEI by XRD. Chemical analysis of the product showed that its SAR was 20.0. Analysis of the mother liquor showed no detectable decomposition of unutilized template after synthesis.

[0088] About 38 g of dealuminated USY zeolite with a SAR of 30 and about 21 g of USY zeolite with a SAR of 10.7 were mixed with 1582 g of ML-P1. To the mixture, about 45 g of N,N-dimethyl-3,5-dimethylpiperidinium template and about 31 g of water were sequentially added. Under stirring, about 34 g of liquid sodium silicate (28.8 wt% SiO2) was slowly poured into the above mixture. The reaction mixture was then heated to about 145°C in a stainless steel reactor under stirring at 200 rpm. After 20-35 hours of crystallization, the solid formed was removed and confirmed to be AEI zeolite by XRD. Chemical analysis of the product showed that its SAR was 20.0. The mother liquor was collected and referred to as the second mother liquor (ML-P2). ML-P2 produced ML-P3 in a similar manner, and, in turn, ML-P3 was used to produce ML-P4, and ML-P4 was used to produce ML-P5.

[0089] The results of these synthetic tests are provided in Table 2.

[0090] Table 2

[0091]

[0092] These results show that the N,N-dimethyl-3,5-dimethylpiperidinium template can be recycled multiple times to increase the total relative yield based on silica and the total relative yield based on SDA. Comparable results can be obtained by varying the percentage of recycled mother liquor, the composition of the gel, the number of recycling repetitions, and reaction parameters such as temperature, time, stirring rate, and pressure. In addition, the gel composition and process parameters can be varied to obtain AEI zeolite crystals with different properties, such as different SAR values.

[0093] Comparative Example: Synthesis of AEI Zeolite Using N,N-Diethyl-2,6-Dimethylpiperidinium

[0094] About 35 g of dealuminated USY zeolite with a SAR of 10.7 was mixed with about 9548 g of water. For this mixture, about 302 g of N, N-diethyl-2,6-dimethylpiperidinium template and about 415 g of liquid sodium silicate (28.8 wt% SiO2) were slowly poured into the above mixture under stirring. The formed mixture was then heated to 145 ° C in a sealed stainless steel reactor under stirring at 200 rpm. After 7 days of crystallization, the formed crystallization mixture was transferred to a separatory funnel. After static sedimentation for 2-4 days, the bottom sediment and the top transparent liquid layer were fully separated. The top transparent liquid layer contained a water-containing bottom portion and a thin oily layer separated into the top portion.

[0095] The solids in the bottom slurry were recovered and confirmed to be AEI by XRD. Chemical analysis of the product showed that its SAR was 25.2. Analysis of the aqueous bottom portion of the mother liquor showed that 35-40% of the unutilized template was decomposed. Analysis of the top oily portion showed that the major molecules were consistent with the decomposition of the template.

[0096] These results show that the mother liquor from the AEI zeolite synthesis reaction using the conventional template N,N-diethyl-2,6-dimethylpiperidinium cannot be effectively reused in a sequential AEI zeolite synthesis batch. In contrast, when N,N-dimethyl-3,5-dimethylpiperidinium is used as the template for the AEI synthesis reaction, the mother liquor can be reused in a sequential AEI zeolite synthesis batch.

Claims

1. A washcoat coating comprising aluminosilicate AEI zeolite crystals having an average aspect ratio (L / D) of less than or equal to 3 and an average crystal size of 1-1.5 μm, and an amount of framework phosphorus of less than 0.1 wt %, wherein the aluminosilicate AEI zeolite crystals have a silica to alumina ratio of 10-35, and the aluminosilicate AEI zeolite crystals are obtained by using a structure directing agent selected from N,N-dimethyl-3,5-dimethylpiperidinium, N,N-dimethyl-2-(2-hydroxyethyl)piperidinium, N,N-dimethyl-2-ethylpiperidinium and 2,2,4,6,6-pentamethyl-2-azabicyclo[3.2.1]octane.

2. The washcoat coating of claim 1, wherein the aluminosilicate AEI zeolite crystals have an average aspect ratio (L / D) of less than or equal to 2.

0.

3. A washcoat according to claim 1, wherein the aluminosilicate AEI zeolite crystals have a silica to alumina ratio of 15-25.

4. A washcoat according to claim 1, wherein the aluminosilicate AEI zeolite crystals contain post-synthesis exchanged ions of one or more transition metals.

5. The washcoat coating according to claim 4, wherein the transition metal comprises at least one metal selected from manganese, iron, cobalt, nickel and mixtures thereof.

6. The washcoat coating of claim 4, wherein the post-synthesis exchanged ions of the one or more transition metals are present in an amount of 0.1-10 wt%.

7. The washcoat coating of claim 1 , wherein the aluminosilicate AEI zeolite crystals contain 0.5-5 wt. % post-synthesis exchanged copper ions, based on the total weight of the zeolite.

Citation Information

Patent Citations

  • Shaped body comprising a microporous material and at least one silicon-containing binding agent method for production and use thereof as catalyst in particular in a method for continuous synthesis of

    CN101326007A

  • Zeolite SSZ-39

    US5958370A

  • Synthesis and use of AEI structure-type molecular sieves

    WO2009117186A1